(untitled) (Research, Society and Development, 2021)
Objective: To identify and analyze scientific production on the use of ultraviolet-C rays for disinfection, decontamination and sterilization, to publish journal articles from 2014 to 2018. Method: Exploratory research with a qualitative and quantitative approach. A survey was conducted in the Web of Science database. Results: 230 scientific articles were retrieved, 2018 had the largest number of articles (29%). United States of America (28%) is the country that generates the most publications making the English language (98%) the most recurrent. The mapping of the distribution of periodical articles showed that 16 (15%) journals concentrated on the publication of 99 (43%) articles. The average evaluation of the applications of ultraviolet-C radiation pointed to the predominance of the use of technology in food (32%) and bacteria (53%) in relation to the survey of microorganisms. Conclusion: Publications on the use of ultraviolet-C technology point to its diversity of application, being used in different filters, such as the food industry and hospital environments.